PENDAMPINGAN PARTISIPASI ORANG TUA DALAM PENDIDIKAN ANAK USIA DINI DI PAUD ARSHELIA PASIR BUNGUR DESA RANCASENGGANG KECAMATAN SINDANGKERTA KABUPATEN BANDUNG BARAT - Saepulloh Saepulloh; Komarudin Komarudin; Awan Gunawan (Jurnal Al Maesarah, 2023)
This Community Research (PkM) aims to describe and explain the importance of parental participation in childcare efforts and to facilitate parental involvement in early childhood education at PAUD Arselia, Kampung Pasir Bungur, Rancasenggang Village, Sindangkerta District, West Bandung Regency. The method used in processing the data using interviews, observation, and documentation with descriptive research data analysis. Analysis techniques data and using data reduction, data presentation, and drawing conclusions. The results showed that (1) the factors that influence the involvement of Arshelia PAUD parents in the participation of children's education include social status factors, family form factors, family development stage factors, and role model factors and (2) the efforts that have been made to facilitate the involvement of people parents in early childhood education at PAUD Arshelia, namely: parenting education, information about children's education, development, and health, learning at home, children's performances, recreation, collaboration with the community, home visits by teachers, and participation in The activity was carried out at PAUD Arshelia Pasir Bungur, Rancasenggang Village.